2013
DOI: 10.1371/journal.pone.0081176
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of VEGFR-2 Expression by sFlt-1 and Low Oxygen in Human Placenta

Abstract: Vascular endothelial growth factor receptor 2 (VEGFR-2), the primary receptor for VEGF, is crucial for normal endothelial function. sFlt-1, a truncated and soluble form of VEGFR-1 which binds and inhibits VEGF, is increased in preeclampsia and is positively regulated by low oxygen. Here, we investigated the effects of sFlt-1 and hypoxia on VEGFR-2 expression and signaling in the human placenta. VEGFR-2 transcript and protein levels were significantly decreased in preeclamptic placentae compared to controls (1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
1
19
0
1
Order By: Relevance
“…Recently, we reported that both sFlt-1 and hypoxia attenuated VEGFR-2 levels in human placenta [5]. Previous findings have shown that sFlt-1 expression is mediated by hypoxia and the transcription factor HIF-1a [3].…”
Section: -Me Treatment Increases Vegfr-2 and Decreases Sflt-1 And Himentioning
confidence: 87%
See 2 more Smart Citations
“…Recently, we reported that both sFlt-1 and hypoxia attenuated VEGFR-2 levels in human placenta [5]. Previous findings have shown that sFlt-1 expression is mediated by hypoxia and the transcription factor HIF-1a [3].…”
Section: -Me Treatment Increases Vegfr-2 and Decreases Sflt-1 And Himentioning
confidence: 87%
“…However, VEGFR-2 is also expressed in the trophoblast layer in human placenta, hypothesized to play a role in trophoblast transformation into invasive intravascular trophoblasts [4]. Recently, we determined another pathway for sFlt-1-dependent vascular dysfunction through a direct and inhibitory interaction with VEGFR-2 [5], suggesting an intricate regulatory system between sFlt-1 and VEGFR-2, the disruption of which may suggest further pathways of vascular and trophoblast dysfunction in PE.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…An increase in local sFlt1 may act in a paracrine/autocrine manner, exacerbating the effects of circulating sFlt1, but may also be part of a physiologic mechanism that participates in vessel repair (32). In addition, we previously reported that increased levels of sFlt1 may reduce VEGFR2 expression by direct heterodimer formation (30). Decreased expression of VEGFR2 may substantially affect a spectrum of cellular functions, including proliferation and apoptosis (5).…”
Section: Discussionmentioning
confidence: 99%
“…sFLT-1, which is mainly produced by trophoblast cells and vascular endothelial cells, is supposed sFLT-1 inhibits proliferation, migration, and invasion of colorectal cancer SW480 cells through vascular mimicry formation suppression to be a major angiogenesis inhibitor with strong anti-angiogenic effect. 3,4 In this study, we applied the colon cancer SW480 cell line which has high VM-forming ability to investigate the effect of sFLT-1 on VM formation.…”
Section: Introductionmentioning
confidence: 99%